Characterization of Polymer Concrete with Different Wastes Additions. (2016) - Barbuta, Marinela; Rujanu, Mircea; Nicuta, Alina
Abstract: A lot of types of wastes pollute today the environment and occupy great soil surfaces. One way for consuming wastes is to obtain green materials. Polymer concrete is a new advanced composite material which is used in construction industry due to its superior properties in comparison with ordinary Portland cement concrete such as: higher mechanical strengths and chemical resistance. The paper characterizes the polymer concrete obtained by adding different types of wastes, such as: argillaceous powder, calcareous powder, marble powder and fly ash to a witness mix obtained by mixing epoxy resin and aggregates in two sorts (0-4 mm and 4-8 mm). The microstructure of polymer concrete was analyzed by electronic scanning. The mechanical properties (compressive strength, flexural strength and split tensile strength) were experimentally determined. The calcareous and fly ash addition in polymer concrete mix improved the mechanical properties. The argillaceous powder addition decreased the values of mechanical strengths in comparison with the witness.